2016
DOI: 10.1094/phyto-11-15-0303-r
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Field-Specific Risk of Soybean Sudden Death Syndrome Using Satellite Imagery in Iowa

Abstract: Moderate resolution imaging spectroradiometer (MODIS) satellite imagery from 2004 to 2013 were used to assess the field-specific risks of soybean sudden death syndrome (SDS) caused by Fusarium virguliforme in Iowa. Fields with a high frequency of significant decrease (>10%) of the normalized difference vegetation index (NDVI) observed in late July to middle August on historical imagery were hypothetically considered as high SDS risk. These high-risk fields had higher slopes and shorter distances to flowlines, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…The importance of crop rotation information for SDS detection in our study suggests that features specific to a study site (e.g., prior knowledge of disease occurrence and intensity, landscape features, environmental inputs, or cultivar susceptibility) may be as important as spectral features. Yang et al [62] used a combination of geographic features and satellite image data to predict SDS risk in commercial soybean fields throughout the state of Iowa. Their field survey data confirmed that information from early-season NDVI values and geographical features (e.g., field slope and distance from water flow lines) were correlated with late-season SDS intensity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of crop rotation information for SDS detection in our study suggests that features specific to a study site (e.g., prior knowledge of disease occurrence and intensity, landscape features, environmental inputs, or cultivar susceptibility) may be as important as spectral features. Yang et al [62] used a combination of geographic features and satellite image data to predict SDS risk in commercial soybean fields throughout the state of Iowa. Their field survey data confirmed that information from early-season NDVI values and geographical features (e.g., field slope and distance from water flow lines) were correlated with late-season SDS intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Our study also did not encode the location of the quadrats relative to each other for the random forest model, and this spatial (distance) information could also be used. Depending on their scale, future studies might potentially include soil types, distance to flowlines [62], and climatic and environmental trends [15].…”
Section: Limitations and Future Workmentioning
confidence: 99%
“…Information technology enabled us to study this disease using a non-traditional approach, which may provide new insight on the sudden occurrence of this disease. Yang et al [146] showed SDS to be a model system in the study of satellite remote sensing for disease detection. This is the first reported case of occurrence of a plant disease that can be seen and identified from satellite due to its unique nature.…”
Section: Conclusion and Future Research Opportunitiesmentioning
confidence: 99%
“…There is no in-season treatment for infected plants, making it important to detect Fv infection to take preventive actions in the next planting cycle [32] and consider impact on yield for the current season. Although risk of Fv infection has been studied [33], a nondestructive method to identify Fv infected soybeans prior to visual symptoms is needed.…”
Section: Introductionmentioning
confidence: 99%